Corticospinal and spinal excitability during peripheral or central cooling in humans. (February 2023) - Talebian nia, M.; Leclerc, C.; Glazebrook, C.; Chopek, J.; Giesbrecht, G.G.
Abstract: Cold exposure can impair fine and gross motor control and threaten survival. Most motor task decrement is due to peripheral neuromuscular factors. Less is known about cooling on central neural factors. Corticospinal and spinal excitability were determined during cooling of the skin (Tsk ) and core (Tco ). Eight subjects (four female) were actively cooled in a liquid perfused suit for 90 min (2 °C inflow temperature), passively cooled for 7 min, and then rewarmed for 30 min (41 °C inflow temperature). Stimulation blocks included 10 transcranial magnetic stimulations [eliciting motor evoked potentials (MEPs) which indicate corticospinal excitability], 8 trans-mastoid electrical stimulations [eliciting cervicomedullary evoked potentials (CMEPs) which indicate spinal excitability] and 2 brachial plexus electrical stimulations [eliciting maximal compound motor action potentials (Mmax )]. These stimulations were delivered every 30 min. Cooling for 90 min reduced Tsk to 18.2 °C while Tco did not change. At the end of rewarming Tsk returned to baseline while Tco decreased by 0.8 °C (afterdrop) (P < 0.001). Metabolic heat production was higher than baseline at the end of passive cooling ( P = 0.01), and 7 min into rewarming ( P = 0.04). MEP/Mmax remained unchanged throughout. CMEP/Mmax increased by 38% at end cooling (although increased variability at this time rendered the increase insignificant, P = 0.23) and 58% at end warming when Tco was 0.8 °C below baseline (P = 0.02). Cooling increased spinal excitability but not corticospinal excitability. Cooling may decrease cortical and/or supraspinal excitability which is compensated for by increased spinal excitability. This compensation is key to providing a motor task and survival advantage. Highlights: Central cooling increases spinal, but not, corticospinal excitability. Increased spinal excitability may compensate for decreased cortical excitability. This compensation may provide a survival advantage during cold exposure.